Operating an industry under conditions of uncertainty: the example of the fish processing industry in Poland - Zieziula, Jolanta; Czapliński, Paweł (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2023)
The fish processing industry continues to be one of the fastest-​growing food industry sectors in Poland. Over the past several years, its sales revenue has increased almost sevenfold and, at the end of 2021, stood at PLN 15.1 billion. In light of this, the present paper aims to assess the economic conditions of the Polish fish processing industry under conditions of increased uncertainty, with a particular focus on identifying the reasons for its persistence and continuity of operations. The primary sources of information were secondary statistical data from IERiGŻ PIB and the results of the author’s qualitative research conducted at selected fish processing enterprises. Our study shows that during the period subjected to detailed analysis (2004 -2022), Polish fish processing enterprises proved to be relatively resistant to periods of increased uncertainty despite the increasing impossibility of predicting all the consequences of the enterprises’ decisions over a longer period, especially in terms of demand and supply. These conclusions relate not only to the uncertainties resulting from cyclical economic conditions but also to those caused by climate change, the COVID-19 pandemic and, more recently, the Russian invasion of Ukraine. The reason for the resilience of fish processing to turbulent and adverse changes in the economic environment likely results from it being at the heart of human needs (the necessity to eat), but the problem is much more complex socially, economically, and also spatially.